2018
DOI: 10.4314/ahs.v18i4.27
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus infection among Human Immunodeficiency Virus (HIV) infected individuals on highly active anti-retroviral therapy in North-Central Nigeria

Abstract: BackgroundCytomegalovirus (CMV) infection is common among HIV-infected individuals. Its contribution to morbidity and mortality became more apparent following introduction of highly active anti-retroviral therapy (HAART) which improved survival among HIV-infected individuals.ObjectivesThis study aimed at determining the prevalence of both active and latent CMV infections among HIV-infected individuals on HAART in Ilorin, Nigeria.MethodsA total of 360 consented HIV-1 patients were recruited for the study. About… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
18
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 31 publications
2
18
0
2
Order By: Relevance
“…Patients in the present study had mean CD4 cell count and ART treatment duration of 958.6±37.8 cells/μl and 6.9±3.4 years respectively, indicating adequate immune response and long duration on ART. Going by the suggestion of Ojide et al, (31) and Udeze et al, (37), the good immunological response of patients in our study and their long duration on ART could possibly explain the non-significant association between prevalence of CMV IgM and CD4 cell count and VL. However, many other studies have shown prevalence of CMV IgM to be significantly associated with CD4 cell count (22,40,41).…”
Section: Discussionsupporting
confidence: 52%
See 4 more Smart Citations
“…Patients in the present study had mean CD4 cell count and ART treatment duration of 958.6±37.8 cells/μl and 6.9±3.4 years respectively, indicating adequate immune response and long duration on ART. Going by the suggestion of Ojide et al, (31) and Udeze et al, (37), the good immunological response of patients in our study and their long duration on ART could possibly explain the non-significant association between prevalence of CMV IgM and CD4 cell count and VL. However, many other studies have shown prevalence of CMV IgM to be significantly associated with CD4 cell count (22,40,41).…”
Section: Discussionsupporting
confidence: 52%
“…Although the prevalence of CMV IgM was higher among patients with high CD4+ cell counts and low VL in our study, this surprisingly, was not statistically significant. Similar studies in Benin (31) and Ilorin (37) in Nigeria, and in Iran (41) also found no statistically significant association between CD4+ cell count values and prevalence of CMV IgM in their study populations, and adduced such findings to the effects of ART and duration of treatment. Patients in the present study had mean CD4 cell count and ART treatment duration of 958.6±37.8 cells/μl and 6.9±3.4 years respectively, indicating adequate immune response and long duration on ART.…”
Section: Discussionmentioning
confidence: 50%
See 3 more Smart Citations